An algorithmic approach to pharmacoeconomic analyses - Sadalagi, Shreyas M.; K. H., Hemanth Kumar; M. S., Kishore (International Journal of Basic & Clinical Pharmacology, 2025)
Pharmacoeconomics is defined as the description and analysis of costs of drug therapy to health care systems and society. There are various methods used, such as cost-minimization (CMA), cost-effectiveness (CEA), cost-utility (CUA) and cost-benefit analyses (CBA). Others include willingness-to-pay (WTP) and incremental net benefit (INB) analysis. However, there is lack of knowledge in the proper application of these in a coordinated fashion. The aim is to create an algorithm for health-care professionals in deciding appropriate treatment in a pharmacoeconomic perspective when multiple treatment options are available, ensuring safe and effective health-care services within limited resources. For this we reviewed various literature on pharmacoeconomics and compiled various analytical methods being used, along with their pros and cons, including when they can be applied and not. We used all this information to prepare the algorithm which goes as follows. Step 1: for the given patient condition, find the minimum effectiveness of treatment required and list out the health interventions which can provide it along with their costs, benefits and utility. Step 2: conduct INB analysis using WTP method to rule out those which the patient cannot afford. Step 3: among others, conduct CUA followed by CBA, CEA and CMA in this order. Step 4: the treatment option which doesn’t get ruled out at the end of these steps should be considered. If sufficient data is available (which is an important limitation), this algorithm can serve as a powerful tool in optimizing health-care interventions, at least in selective health-care setups.